Individual and facility level factors influencing timely antenatal care initiation in Ethiopia: A multilevel analysis of the 2021/2022 ESPA data - Addisu Alehegn Alemu; Alec Welsh; Theodros Getachew; Marjan Khajehei (PLoS ONE, 2025)
Background Antenatal care (ANC) is a package of healthcare services for pregnant women that improves the health of both the women and their unborn babies, with a minimum of eight times and most effective when initiated within the first 12 weeks. This study aimed to assess the magnitude and factors associated with timely ANC initiation among pregnant women attending their first ANC visit during their most recent pregnancy in Ethiopia. Methods We analysed weighted data from 2,037 pregnant women who attended their first ANC visit during their most recent pregnancy, extracted from the 2021/2022 Ethiopian Service Provision Assessment. We fitted a multilevel mixed-effects logistic regression model to examine individual and facility level factors influencing timely ANC initiation, which was calculated in weeks. We reported descriptive statistics using frequencies and percentages, and regression results using adjusted odds ratios (AORs) with 95% confidence intervals (CIs). We conducted all analyses using STATA version 16 software. Results The magnitude of timely ANC initiation in Ethiopia was 14.9%, with a mean gestational age at initiation of 22 weeks. Primary education (AOR = 1.74, 95% CI: 1.08, 2.82), partner involvement (AOR = 1.42, 95% CI: 1.03, 1.96), and attending non-public facilities (AOR = 2.49, 95% CI: 1.45, 4.28) were associated with higher odds of timely ANC initiation. Conversely, bypassing nearby facilities (AOR = 0.44, 95% CI: 0.30, 0.64) and attending facilities in large central regions (AOR = 0.24, 95% CI: 0.15, 0.40) or small peripheral regions (AOR = 0.27, 95% CI: 0.13, 0.52) were associated with lower odds of timely ANC initiation. Conclusion One in seven pregnant women in Ethiopia initiated ANC within the first 12 weeks of pregnancy, far below the World Health Organization recommendation that all pregnant women should begin ANC within this period. Timely ANC initiation could be explained by factors related to women, their partners, and healthcare facilities. Policy interventions should prioritise women’s education, partner involvement, utilisation of nearby available healthcare facilities, community awareness to improve timely ANC initiation in Ethiopia.